“Brigas de beleza”: a construção de consensos no fórum de comunidades de política pública do território rural Vale do Rio Pardo – RS - Silva, Taciane Lais da (2017)
The purpose of this dissertation is to study the Vale do Rio Pardo Rural Territory (TRVRP), here characterized as a community public policy forum, which was recognized as a Rural Territory integrated into the National Program for Sustainable Development of Rural Territories (PRONAT)by the Ministry of Agrarian Development (MDA) in 2013, defining it with a geographical delimitation that was not demanded by the social actors. The TRVRP unites two distinct macro regions, the South region of the Territory (referring to the Pardo River Valley) and the North (referring to the upper Serra do Botucaraí region, included in the new territorial delimitation made by MDA). In view of the above, the main objective of this study was to analyze the relationships that were built between the agents that defined a certain conformation, territorial management and the public policy community forum. Specifically, it was sought to identify the main social actors that lead to the PRONAT social concertation in the TRVRP; to find out what are the main tensions and to analyze the characteristics of this social protagonism assumed by these actors. For this, it has been used as reference a study conducted by Paulo Niederle and Cátia Grisa in the year of 2013, in which the authors identified some guiding questions to carry out these case studies. Thus, the focus of the analysis was centered in the intersections between what, from the native point of view, is conceptualized as politics, using as a method of cognitive analysis t approach This analysis has as its main merit the perception built by Bruno Jobert and Ève Fouilleux, which is based on the manner in which disputes and negotiations are related to the production of public policy references, highlighting where they occur in forums / arenas, as well as the form of decoding the different actors create and the representations that maintain these references. To this end, six social actors were identified and characterized as spokespersons, who were the protagonists in the TRVRP tensions negotiations. During the research, three critical moments were analyzed, which refer to the main stresses brought for reflection: the lack of cohesion and territorial identity and the need to divide the Territory, the Multi-territorial Conference on Technical Assistance and Rural Extension (ATER), and the Discussions and tensions in the disputes of the investment proposals of the Infrastructure Program (PROINF). This process of immersion with the object of study occurred due to the fact that the author of this dissertation is part of the team of the Extension and Territorial Development Center (NEDET) that advises the Territorial Board of TRVRP. Therefore, the instruments used in the TRVRP ideas production forum served to weaken the traditional forms of domination perpetuated in the Territory. In addition, it succeeded in favoring the empowerment of social actors who were previously submissive to the will of the State. However, it is necessary to continue this process and identify the changes of spokespersons over time. Certainly, the emergence of new ideas will be linked to struggles of legitimizing new actors who will replace the former spokespersons of the TRVRP public policy community forum.